2021
DOI: 10.1021/acsomega.1c04561
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Rapid Fire Zone Sealing and Explosion Venting Characteristics of an Explosion Venting Door Using a Large-Diameter Explosion Pipeline

Abstract: To study the law of influence of an explosion venting door on gas explosion characteristics and verify its venting effect and fast sealing performance, a large-sized explosion pipeline experimental system was used. The gas explosion tests were carried out under the conditions of 5.5, 7.5, 9.5, and 11.5% gas concentration. The gas explosion characteristic parameters were measured by a data acquisition system. The laws of change in characteristic parameters and the flame-proof effect were analyzed. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…In recent years, with the promotion and popularization of coalbed methane extraction and gas surface utilization, the frequency of accidents during the transportation of gas has gradually increased [8]. On 26 October 2015, a gas extraction pipeline explosion occurred in the Wuyang Coal Mine in Shanxi Province, leading to the death of one miner [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the promotion and popularization of coalbed methane extraction and gas surface utilization, the frequency of accidents during the transportation of gas has gradually increased [8]. On 26 October 2015, a gas extraction pipeline explosion occurred in the Wuyang Coal Mine in Shanxi Province, leading to the death of one miner [9].…”
Section: Introductionmentioning
confidence: 99%
“…While bringing convenience to people, natural gas also poses greater safety risks. In recent years, some natural gas explosion accidents have occurred frequently, causing serious casualties and social and economic losses. At present, there are more studies on the combustion and explosion problems in the safe transportation process of large aspect ratio pipelines, concentrating on the study of the influence of characteristic parameters such as pressure relief ratio, opening pressure, opening time, and blocking ratio on the natural gas-constrained explosion process, and it was found that when the blockage ratio is set reasonably, the power generated by the explosion can be effectively reduced. Given this, how to scientifically and effectively set the shape of the vent, the blockage ratio and opening position, and other characteristic parameters have become the focus of research by many scholars.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of the coal is underground-mined. 6 8 Coal and gas outbursts, rock bursts, gas explosions, and other dynamic disasters become more severe as the mining depth gradually extends. After the gas gushes out, the gas concentration in the surrounding environment will increase.…”
Section: Introductionmentioning
confidence: 99%
“…Coal consumption still dominates the energy structure of China and has mined 353.2 million tons of coal during production, accounting for 45.6% of the global production in 2020, and it is the world’s largest coal producer. More than 90% of the coal is underground-mined. Coal and gas outbursts, rock bursts, gas explosions, and other dynamic disasters become more severe as the mining depth gradually extends. After the gas gushes out, the gas concentration in the surrounding environment will increase .…”
Section: Introductionmentioning
confidence: 99%